Pengaruh Persepsi Harga dan Service Quality terhadap Kepuasan Konsumen : Survei pada Konsumen Popo Kopitiam Kota Tasikmalaya - Fahmi Sidik; Depy Muhamad Pauzy; Arif Arif (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of price perception and service quality on customer satisfaction at Popo Kopitiam Tasikmalaya. The research method used is a survey with a quantitative approach. Data were collected through distributing questionnaires to 90 respondents who are active customers of Popo Kopitiam. Data analysis was conducted using multiple linear regression to determine the simultaneous and partial effects between the independent and dependent variables. The results showed that simultaneously, price perception and service quality have a significant effect on customer satisfaction. Partially, price perception has a significant effect on the level of customer satisfaction, indicating that assessing price according to product quality can increase satisfaction. Similarly, good service quality significantly influences customer satisfaction, indicating the importance of fast, friendly, and professional service. These findings indicate that the combination of competitive prices and optimal service is a major factor in building customer satisfaction at Popo Kopitiam Tasikmalaya.